PROSEDUR PEMERIKSAAN MRI WRIST JOINT PADA KASUS DISRUPSI DISTAL RADIOULNAR JOINT DENGAN MENGGUNAKAN GENU COIL - Hendriawan; M. Irwan Katili; Dartini (Perhimpunan Radiografer Indonesia (PARI), 2019)
ABSTRACT Background: Procedure of MRI wrist joint examination on disruption case of Distal Radioulnar Joint at radiology installation of RS Panti Rapih Yogyakarta using genu coil. The purpose of this research is to know the procedure of MRI wrist joint examination in DRUJ disruption case using genu coil, to know the reason for the use of genu coil for the examination of wrist joint and to know the reason for adding the PD FatSat sequence and STIR on MRI wrist joint examination. Methods: The type of this research is qualitative research with case study approach. Data collection by observation, interview, and documentation. This study was conducted from February to June 2018. Respondents in this study were 1 radiologist, 1 sending doctor and 3 radiographers, and the subjects of this study is 1 patient with diagnoses having DRUJ disorder or disruption. Data analysis in this research using interactive model. Result: The results of this study showed that the procedure of MRI wrist joint examination in DRUJ disruption case at radiology installation of RS Panti Rapih using genu coil and using 10 examination sequences were: axial PD FatSat, axial T1 FSE, axial T2 FSE, axial STIR irFSE, coronal PD FatSat, coronal T1 FSE, coronal T2 FSE, coronal STIR irFSE, sagital PD FatSat, dan sagital T1 FSE. The reason for using genu coil on the MRI wrist joint examination because genu coil can deliver the signal well, so it can produce a good picture, and because the size of the coil is large then has a wide coverage so that all of parts wrist joint is covered. The reason for the addition of FatSat and STIR sequences is FatSat to suppress fat around the wrist joint so the odim fluid or effusion fluid in the joints can be seen more clearly, and STIR sequence has a very high ability to exhibit pathological disorders. Conclusion : Procedure for MRI examination of wrist joints in disruption case of DRUJ using genu coil at Radiology Installation of Panti Rapih Hospital Yogyakarta.The reason for the wrist joint MRI examination using the coil genu becouse the result of wrist joint examination so far can produce a good picture. And the reason for the wrist joint MRI examination in disruption of DRUJ case was added by the Fat Sat and STIR sequences, which were to suppress the fat around the wrist joint so the liquid odim or effusion fluid in the joint could be seen more clearly.